Interactional Order and Constructed Ways of Seeing with Touchless Imaging Systems in Surgery - O'Hara, Kenton; Gonzalez, Gerardo; Penney, Graeme; Sellen, Abigail; Corish, Bob; Mentis, Helena; Varnavas, Andreas; Criminisi, Antonio; Rouncefield, Mark; Dastur, Neville; Carrell, Tom (Journal of Computer Supported Cooperative Work, 2014)
While surgical practices are increasingly reliant on a range of digital imaging technologies, the ability for clinicians to interact and manipulate these digital representations in the operating theatre using traditional touch based interaction devices is constrained by the need to maintain sterility. To overcome these concerns with sterility, a number of researchers are have been developing ways of enabling interaction in the operating theatre using touchless interaction techniques such as gesture and voice to allow clinicians control of the systems. While there have been important technical strides in the area, there has been little in the way of understanding the use of these touchless systems in practice. With this in mind we present a touchless system developed for use during vascular surgery. We deployed the system in the endovascular suite of a large hospital for use in the context of real procedures. We present findings from a study of the system in use focusing on how, with touchless interaction, the visual resources were embedded and made meaningful in the collaborative practices of surgery. In particular we discuss the importance of direct and dynamic control of the images by the clinicians in the context of talk and in the context of other artefact use as well as the work performed by members of the clinical team to make themselves sensable by the system. We discuss the broader implications of these findings for how we think about the design, evaluation and use of these systems.